AB0021 VARIABILITY OF THE RS333 IN LUPUS ERYTHEMATOSUS PATIENTS FROM THE POLISH POPULATION. (2nd June 2020) - Skonieczna, K.; Mlicka, D.; Woźniacka, A.; Czajkowski, R.; Robak, E.; Gawrych, M.; Duleba, A.; Grzybowski, T.
Abstract : Background: There are several subtypes of Lupus Erythematosus (LE), which may be limited to the skin (eg. Discoid Lupus Erythematosus, DLE) or involve multiple organ dysfunctions ( Systemic Lupus Erythematosus, SLE). LE is an autoimmune disease that is influenced by genetic and environmental factors. Despite some genetic changes between DLE and SLE were previously shown, the complete genetic background of DLE is still unresolved [1]. Functional C-C chemokine receptor 5 (CCR5) receptor can be associated with the inflammation in LE patients. Importantly, the 32 base pairs (bp) deletion in CCR5 gene (rs333) leads to a nonfunctional receptor. Previous studies have shown that this mutation may have a protective effect on the development and progression of SLE [2, 3]. Thus it was important to investigate whether 32 bp deletion in rs333 is also associated with DLE development. Objectives: The aim of this study was to investigate the variability of the CCR5 gene, within a polymorphic locus rs333 in SLE and DLE patients from the Polish population. Methods: 120 LE patients (77 SLE patients and 43 DLE patients) and 100 healthy persons were recruited to the study from the Polish population. DNA was isolated from blood or buccal swabs. rs333 was genotyped by using polymerase chain reaction (PCR). Statistical significance of the differences between patient and control groups in both allele and genotype frequencies were calculated using Chi-Squared test with Yates correction or two tailed Fisher's exact test. Results: Deletion allele of the rs333 was significantly less frequent among DLE patients than healthy persons (p = 0.0171). Also the heterozygotes occur significantly less frequent within DLE patients group than in healthy individuals (p = 0.0375). Moreover, homozygotes without deletion in rs333 were found significantly more frequent in persons diagnosed with DLE than in healthy volunteers (p = 0.0214). In contrast, the differences in allele or genotype frequencies between SLE patients and healthy controls were not statistically significant (p > 0.05). Moreover, the rs333 variability was not associated with clinical symptoms of LE patients (p > 0.05). Conclusion: Summarizing, the results obtained in this study suggest that the 32 bp deletion within rs333 could be a protective factor, that reduce the risk for DLE but not SLE development in the Polish population. However, due to the low statistical power of the obtained results, further studies on larger groups of patients and controls are needed to acquire more reliable data. References: [1]Skonieczna K, Czajkowski R, Kaszewski S, Gawrych M, Jakubowska A, Grzybowski T. (2017) Genetic similarities and differences between discoid and systemic lupus erythematosus patients within the Polish population. Postepy Dermatol Alergol. 34: 228-232. [2]Schauren JS, Marasca JA, Velt TD, Monticielo OA, Xavier RM, Brenol JCT et al (2013) CCR5 delta32 in systemic lupus erythematosus: implications for disease susceptibility and outcome in a Brazilian population. Lupus 22:802–809. [3]Martens, H.A., Kallenberg, C.G. & Bijl, M. (2009) Role of CCR5 Delta32 bp deletion in RA and SLE. Autoimmunity, 42, 260. Acknowledgments: KS was supported by the "Excellence Initiative - Research University" programme as a member of the team "Bioinformatics in medical & population genomics". Disclosure of Interests: Katarzyna Skonieczna Grant/research support from: KS was supported by the "Excellence Initiative - Research University" programme as a member of the team "Bioinformatics in medical & population genomics"., Dominika Mlicka: None declared, Anna Woźniacka: None declared, Rafał Czajkowski: None declared, Ewa Robak: None declared, Mariusz Gawrych: None declared, Anna Duleba: None declared, Tomasz Grzybowski: None declared